High Level of Conservation of Mitochondrial RNA Editing Sites Among Four Populus Species. Issue 3 (1st March 2019) - Brenner, Wolfram Georg; Mader, Malte; Müller, Niels Andreas; Hoenicka, Hans; Schroeder, Hilke; Zorn, Ingo; Fladung, Matthias; Kersten, Birgit
Abstract: RNA editing occurs in the endosymbiont organelles of higher plants as C-to-U conversions of defined nucleotides. The availability of large quantities of RNA sequencing data makes it possible to identify RNA editing sites and to quantify their editing extent. We have investigated RNA editing in 34 protein-coding mitochondrial transcripts of four Populus species, a genus noteworthy for its remarkably small number of RNA editing sites compared to other angiosperms. 27 of these transcripts were subject to RNA editing in at least one species. In total, 355 RNA editing sites were identified with high confidence, their editing extents ranging from 10 to 100%. The most heavily edited transcripts were ccmB with the highest density of RNA editing sites (53.7 sites / kb) and ccmFn with the highest number of sites (39 sites). Most of the editing events are at position 1 or 2 of the codons, usually altering the encoded amino acid, and are highly conserved among the species, also with regard to their editing extent. However, one SNP was found in the newly sequenced and annotated mitochondrial genome of P. alba resulting in the loss of an RNA editing site compared to P. tremula and P. davidiana . This SNP causes a C-to-T transition and an amino acid exchange from Ser to Phe, highlighting the widely discussed role of RNA editing in compensating mutations.